From mass to protest: Female Catholic workers inside Asturias strikes and during the First of May celebrations (1956-1965) - Martín Gutiérrez, Sara (Huarte de San Juan. Geografía e Historia, 2020)
This article shows the protest of Catholic female workers from the hoacf during the Francoism. From the intersectional perspective and behind oral testimonies, this paper explores the identities inside the hoacf. It also explores the agency in different occurrences inside the workers’ sociability. In that way, this article researches on the aspects that influenced female workers in order to participate on 1962 strikes and during the First of May celebrations. This paper approaches a comparative agency between actors and actresses from Social Catholicism over workers’ movement mobilization in Spain. Finally, this research analyses how their interventions where crossed by a strong class identity and by a «worker dignity» ideal disseminated by the Acción Católica Obrera.